IMPLEMENTASI KEBIJAKAN INTEGRASI SISTEM PERIZINAN BERUSAHA DALAM MENINGKATKAN PELAYANAN PUBLIK DI DIREKTORAT PESTISIDA KEMENTERIAN PERTANIAN - Dyah Ayu Indri Nurani (ITB AAS Indonesia Surakarta, 2026)
This study aims to analyze the implementation of the integration policy between the Online Single Submission (OSS) system and the SIMPEL1 application in the pesticide licensing process at the Ministry of Agriculture of Indonesia. Using Larry N. Gerston’s (2010) public policy implementation framework. A qualitative approach was employed, utilizing interviews, document and field observations. The findings reveal that the integration of OSS and SIMPEL1 has not been optimally implemented. The key challenges include misalignment between the generic structure of OSS and the technical specificity required in the pesticide sector, limited human resource capacity and training, unbalanced workloads due to insufficient personnel, and weak monitoring and evaluation mechanisms.